Aproveitamento da casca do coco verde (Cocos Nucifera, L.) para produção de celulases - Oliveira, Simone Lopes do Rêgo de (2010)
Enzyme production by fermentative process is a broad field of biotechnology. In recent decades, there has been an increasing trend in the use of solid-state fermentation (SSF) for the production of some enzymes, especially those involved in the degradation of vegetables complex macromolecules. Regarding the enzyme market Brazil is consumer of imported products. In this scenario, the coconut shell emerges as a strategic raw material to reach the production of enzymes in the country. Thus, it is important to further on the use of coconut green shell powder as substrate for cellulolytic enzymes of interest in the food industry. Cellulase producing fungi used in this study were isolated from coconut shell. The results of enzyme activity obtained with the isolated strains from coconut shell were compared in terms of production capacity of cellulases with strains of Trichoderma polysporum, T. viride, T. reesei NRRL 11460 and Aspergillus niger NRRL 2001. From the results, the coconut shell waste can be considered a good inducer for cellulase production . The strain isolated from coconut shell (CZ01) is a good producer under solid-state fermentation because higher enzyme activity was obtained with its crude enzyme extract when compared with other enzyme producers, including a patented strain of T. reesei Rut C-30 (NRRL 11460), using the same inducer substrate. It is also worth mentioning that the majority of cellulase reported in the scientific literature are obtained under conditions of acidic pH and in this study the maximum enzyme activity was obtained at pH close to neutral (range 6.0 to 6.5). Therefore, the isolated and selected strain from the coconut shell (CZ01) showed good enzyme activity when compared with results obtained by other strains reported in the scientific literature, being therefore a very promising strain for the cellulase production enabling the use of this agroindustrial wastes.